1999
DOI: 10.1073/pnas.96.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Disordered water within a hydrophobic protein cavity visualized by x-ray crystallography

Abstract: Water in the hydrophobic cavity of human interleukin 1␤, which was detected by NMR spectroscopy but was invisible by high resolution x-ray crystallography, has been mapped quantitatively by measurement and phasing of all of the low resolution x-ray diffraction data from a single crystal. Phases for the low resolution data were refined by iterative density modification of an initial f lat solvent model outside the envelope of the atomic model. The refinement was restrained by the condition that the map of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
135
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 25 publications
6
135
3
Order By: Relevance
“…Despite the general success of hydrophobic models (1-3), attempts to determine the interior ''hydrophobicity'' of proteins have often given conflicting results (2,(4)(5)(6)(7)(8)(9)(10). Some proteins seem to require water at least transiently in nonpolar cavities for their function (11,12).…”
mentioning
confidence: 99%
“…Despite the general success of hydrophobic models (1-3), attempts to determine the interior ''hydrophobicity'' of proteins have often given conflicting results (2,(4)(5)(6)(7)(8)(9)(10). Some proteins seem to require water at least transiently in nonpolar cavities for their function (11,12).…”
mentioning
confidence: 99%
“…X-ray crystallography has observed the presence of water within protein cavities of varying hydrophobicity which can affect the strength of protein−ligand binding. 21,22 Simulations have also shown that water can be sequestered between hydrophobic plates with a relatively small centralized hydrophilic patch. 23 Ambiguity also remains as to how dry contact is established underwater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This important finding implies that the product water indeed takes a very specific route out of the heme a 3 ͞Cu B site, which is next to a hydrophobic cavity that is predicted to at least transiently hold several water molecules (2-4, 17, 18), although they have not been observed in the crystal structures. Hydrophobic cavities in proteins may indeed contain water that is sufficiently mobile to escape detection by x-ray crystallography but may be found by NMR spectroscopy (19). However, there is no obvious route in the static x-ray structures of cytochrome c oxidase by which the product water would be specifically transferred from the heme a 3 ͞Cu B center to the Mg(Mn) site, although a transfer pathway further out from the latter site has been described (20).…”
mentioning
confidence: 99%